Female Representation but Male Rule? Party Competition and the Political Glass Ceiling - Olle Folke; Johanna Rickne (Research Institute of Industrial Economics (IFN), 2012)
A large literature has studied the context that affects womens numerical representation, but few have moved beyond numbers to study the drivers of a gender gap in political influence among elected politicians. Using panel data for the careers of 35.000 Swedish municipal politicians over six election cycles we first document the said gender gap. Women are substantially less likely to be re-elected for office, which is the most important pre-condition for obtaining influential appointments. Turing to the determinants we find that supply factors, primarily family responsibilities, explain some of this gap. Meanwhile, demand factors such as experience, age, education and income do not. Finding that competition between political parties closes the gap, we argue that a negative bias against women among party selectors thrives in contexts where meritocracy is not enforced. Positive correlations between competition and measures of competence for elected politicians of both genders further support this conclusion.
Keywords: H10; J16; J21; J45; 330; Careers in politics; Political competition; Supply of politicians